Implementative Design Professional Learning Community (PLC) To Improve Performance of Educators - Muhammad Mahfud (EDUCATIO : Journal of Education, 2018)
This research study focused on the design shape PLC held at Foundation of Darul Ihsan and its relation with the improved performance of educators. Implementative designs are applied in compliance with the five major elements PLC (focuson learning, collaborative culture, collective inquiry into research, professional learning by doing, and all the members mutually accountable for targeted result). Implementation of PLC refers to the six strategies that have been designed that is reflective dialogue, de-privatization of practice, collective focus on student learning, collaboration, shared norms and values, and optimalization of golden triangle. This last strategy Becomes a different matter with the implementation of PLC in general. optimization of the golden triangle in question is do the synchronization between the three elements play items, namely education actors educators, students, and parents. Synchronizing the form of collaborative engagement and cultivation of a sense of belonging between elements on the basis of trust and sincerity and monotheism.